2019
DOI: 10.1038/s41598-019-52186-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction between DARC and SDF-1 on erythrocytes and their precursors

Abstract: The Duffy Antigen Receptor for Chemokines (DARC) is expressed on erythrocytes and on endothelium of postcapillary venules and splenic sinusoids. Absence of DARC on erythrocytes, but not on endothelium, is referred to as the Duffy negative phenotype and is associated with neutropenia. Here we provide evidence that stromal cell-derived factor 1 (SDF-1), the chemokine that restricts neutrophil precursors to the bone marrow, binds to erythrocyte progenitors in a DARC-dependent manner. Furthermore, we show that SDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…The recombinant ACKR1 fragment produced in bacteria lacks those modifications, which are more likely to enhance CXCL12 binding than to diminish or alter it. Our findings not only confirm a recent report that CXCL12 is an ACKR1 ligand ( 55 ) but also importantly modify its conclusions as monomeric CXCL12 is not a potent ligand of ACKR1. Our data open a possibility that other chemokines that apparently fail to compete with canonical ACKR1 ligands for binding might still bind ACKR1 in physiologically relevant contexts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The recombinant ACKR1 fragment produced in bacteria lacks those modifications, which are more likely to enhance CXCL12 binding than to diminish or alter it. Our findings not only confirm a recent report that CXCL12 is an ACKR1 ligand ( 55 ) but also importantly modify its conclusions as monomeric CXCL12 is not a potent ligand of ACKR1. Our data open a possibility that other chemokines that apparently fail to compete with canonical ACKR1 ligands for binding might still bind ACKR1 in physiologically relevant contexts.…”
Section: Discussionsupporting
confidence: 87%
“…CXCL12-WT and, to a greater extent, CXCL12-LD lead to broadening of additional ACKR1 N-term peaks with many of these located in the 50s region of ACKR1 N-term residues. Previous reports provide contradicting claims regarding the interaction or lack thereof of CXCL12 with ACKR1 ( 54 , 55 ). Our analysis of the ACKR1 N-term spectra suggests that ACKR1 N-term can bind CXCL12-LM, CXCL12-WT, and CXCL12-LD with potentially substantial differences in affinity and stoichiometry.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…During reticulocyte maturation a spectrum of different morphological configurations occurs. These processes are as yet ill-defined mechanistically but involve restructuring of membrane protein complexes and their dynamic interaction with the underlying spectrin cytoskeleton, as well as regulation by post-translational protein modifications, loss of specific proteins through vesicle release (e.g., AQP1 and CD71) and shear stress signaling [ 36 , 37 , 38 , 39 ]. The presence of proto-biconcave cells, meaning a large biconcave cell with irregular borders, suggests a more advanced maturation stage of the reticulocytes formed at three percent O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSPC mobilization is tightly controlled by an interplay between cell–cell interactions and chemokines (e.g., SDF1) and also regulated by atypical chemokine receptor (DARC, containing the duffy antigen) expression on erythroid cells [ 43 ]. We have recently shown that DARC expressed on nucleated erythroblast binds SDF1 but that this is lost upon reticulocyte maturation [ 39 ]. Increased erythroid mass due to hypoxia-induced stress erythropoiesis may signal mobilization of HSPC.…”
Section: Discussionmentioning
confidence: 99%